Consonant Sound Alternations in Speech: A Case Study of Students with Class III Malocclusion Condition - Ferdiansyah, Dimas; Mardhia, Putri Hanin; Syukri, Masitha Ahmad (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
The position of the tongue and teeth as the articulatory settings forms sounds during speech production. Understanding this, this study aims to identify the sound alternation outcomes most affected by changes in jaw position, namely Class III malocclusion (underbite). As participants in this study, Universitas Airlangga students are required to perform reading tasks focusing on consonant sounds in their first language, Indonesian. Qualitative research is used to analyze sound alternation, drawing on theories from Field (2004) in the Psycholinguistics study and Dardjowidjojo (2009) in the Phonetics study. Voice recordings of reading exercises using three texts were collected from the two participants. Analysis of this data showed that both individuals frequently substituted the /s/ and /z/ sounds, accounting for the majority (76.25%) of all sound changes observed. Furthermore, the study identified other sound alterations, including insertions (7.5%), deletions (12.5%), and metathesis (3.75%). These results suggest that an underbite affects the production of various sounds, not just the substitution of the sibilants /s/ and /z/. The researchers expect this study to contribute to psycholinguistic research by providing sound alternative surveys of people with Class III malocclusion.